دور شركات الخدمات البترولية على إدارة المشاريع النفطية في مدينة أربيل - Tavga Qadir Omer; Karwan Khalid Hamad; Ahmed Hoshiar Hamzah (QALAAI ZANIST JOURNAL, 2019)
The research aims to study the role of oil service companies in managing oil & gas projects within the oil & gas companies for the period 2017-2018, as it is an exploratory study in a sample of oil service companies in the city of Erbil. It includes the services of oil companies, an independent variable and affects the management of the oil sector. The research also aims to achieve its goals by relying on the two approaches, the first approach is the descriptive approach, i.e. describing the variables and identifying the oil companies along with the number of oil service companies (5). The questionnaire was distributed to them and it was relied upon as a tool to collect data and information, and then we developed a hypothetical model based on a set of assumptions, including: - 1. There is a significant relationship with statistical significance for the services provided by the oil companies in managing the petroleum projects. 2. There is a statistically significant effect of the services provided by oil companies on the management of petroleum projects. 3. The role of the petroleum department varies with the services provide by the petroleum companies. Also, reliance on the second approach is the analytical approach, that is, to analyze the data and information collected and to use them to analyze the result